Hypertranslation - Vidal Claramonte, Mª Carmen Àfrica 1964-; Lee, Tong-King ca. 20./21. Jh (Cambridge University Press, 2024)
Hypertranslation refers to a vast and virtual field of mobile relations comprising the interplay of signs across languages, modes, and media. In hypertranslation, the notions of source/target, directionality, and authenticity are set in perpetual flow and flux, resulting in a many-to-many interactive dynamic. Using illustrations drawn from a wide range of literary and artistic experiments, this Element proposes hypertranslation as a theoretical lens on the heterogeneous, remediational, extrapolative, and networked nature of cultural and knowledge production, particularly in cyberspace. It considers how developments in artificial intelligence have led to an expansion in intersemiotic potentialities and the liquidation of imagined boundaries. Exploring the translational aspects of our altered semiotic ecology, where the production, circulation, consumption, and recycling of memes extend beyond human intellect and creativity, this Element positions hypertranslation as a fundamental condition of contemporary posthuman communication in Web 5.0 and beyond
Title from publisher's bibliographic system (viewed on 29 Nov 2024)
Keywords: Translating and interpreting / Data processing; Machine translating